Implementasi Nilai-Nilai Pancasila Dalam Pendidikan Kewarganegaraan Sebagai Pondasi Karakter Generasi Muda Dalam Berbangsa Dan Bernegara - Sri Wati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In the of history, Pancasila as a normative foundation has been deeply rooted. Pancasila has not been widely implemented into the character of the younger generation. To explore how young people today interpret Pancasila, the author tries to explain several important points in implementing the values of Pancasila for the character of the younger generation. How does a young generation interpret Pancasila in everyday life and what are their views as a figure of the younger generation.